Health versus Price: The Mediating Role of Attitudes in Organic Food Purchasing Decisions - Andika Andika; Della Nanda Luthfiana; Ridwan Ridwan; Bestina Lendi Nur Khotimah (Dinasti Publisher, 2023)
Despite the rising global trend in organic food sales, they represent only 5% of the total food sales, a pattern mirrored in Indonesia. While Indonesians recognize the advantages of organic food, its perceived high cost remains a consumption barrier. This study employs the Theory of Reasoned Action (TRA) to explore determinants affecting consumers' Willingness to pay a premium for organic food, focusing on health concerns and price consciousness and considering the Attitude towards organic food as a mediating variable. Data from 230 Indonesian organic food market respondents was analyzed using Structural Equation Modeling (SEM). The results show that health concerns and price consciousness significantly influence consumer attitudes towards organic food. However, only price consciousness directly affects the Willingness to pay more, while health concerns do not. In contrast, positive attitudes towards organic food are essential in linking health concerns and price awareness with Willingness to pay more. These insights can assist industry stakeholders in devising more effective marketing and pricing strategies to increase organic food adoption, grow the industry, support sustainable agriculture, and benefit consumers and the environment.